Approximate analytical solutions of the Klein-Gordon equation by means of the homotopy analysis method - A.K. Alomari; Mohd Salmi Md Noorani; Roslinda Mohd Nazar (Penerbit ukm, 2008)
In this paper, the homotopy analysis method (HAM) is implemented to give approximate and analytical solutions for the Klein–Gordon equation. The auxiliary parameter ℏ in the HAM solutions has provided a convenient way of controlling the convergent region of series solutions. This problem shows rapid convergence of the sequence constructed by this method to the exact solution. Moreover, this technique reduces the volume of calculations by avoiding discretization of the variables, linearization or small perturbations